Patterns of aldosterone, renin level and aldosterone/renin ratio in young hypertensive patients - Saha, Sumanta Kumer; Moni, Tamanna Tabassum; Rezaul Kadir, M. (International Journal of Research in Medical Sciences, 2024)
Background: Hypertension is a common disease that affects a vast and diverse patient group. Aldosterone, the primary human mineralocorticoid, is increasingly recognized as playing a key role in cardiovascular morbidity, and its involvement in hypertension has lately been evaluated by studies. It is estimated that it accounts for up to 13% of all hypertension patients and 20% of resistant hypertension cases. This study aimed to observe the patterns of aldosterone, renin level, and aldosterone/ renin ratio in young hypertensive patients. Methods: This was a retrospective observational study and was conducted in the Department of Medicine Popular Medical College Hospital, Dhaka, Bangladesh during the period from June, 2023 to December, 2023. In our study, we included 124 hypertensive patients who visited the outdoor department of medicine of our hospital. Results: In our study, we found mean age was 33.38±4.49 years. The majority (75%) of our patients were male. The mean SBP and DBP were 136.77±17.54 and 88.58±10.72 mmHg respectively. The mean aldosterone level was 148.74±125.91 pmol/L. The mean plasma renin activity and aldosterone to renin ratio were 10.03±12.04 ng/mL/hr and 22.98±28.66 respectively. Conclusions: In our study, we aimed to determine the pattern of ARR ratio in young hypertensive patients. We found that aldosterone renin ratio (ARR) levels play a crucial role in identifying the etiological patterns of young hypertensive patients e.g. Conn's syndrome, Liddle's syndrome, etc.